The first multiple center prospective study of rhFSH CTP in patients undergoing assisted reproductive technology in China - Longmei Wu; Huayan Yin; Lingfang Guan; Guanjian Li; Junqiang Zhang; Qunshan Shen; Xiaoqing Ni; Chao Wang; Tianjuan Wang; Hao Geng; Chuan Xu; Yunxia Cao; et al. (Scientific Reports)
Abstract We assessed the safety and efficacy of rhFSH-CTP, a novel long-acting FSH agent, in controlled ovarian hyperstimulation for patients undergoing ART. A multi-center, open-label, randomized, positive-control, non-inferiority clinical trial was conducted. The study consisted of a phase III randomized design, with a 1:1 ratio favoring the rhFSH-CTP group over the control group. Eligible patients in the rhFSH-CTP group received a single dose of rhFSH-CTP at 100–150 µg for the first 7d of stimulation following a gonadotropin-releasing hormone antagonist protocol. In total, 142 and 141 patients received rhFSH-CTP and rhFSH, respectively. At a confidence interval of 95%, the difference in the number of oocytes (1.13–4.22, 2.67) suggested that rhFSH-CTP was not inferior to rhFSH. Additionally, the top-quality embryos, implantation rates, and pregnancy outcomes were similar between the two groups (P > 0.05). In the rhFSH-CTP group, no cases of severe OHSS were observed, which was a significant improvement compared to the 1.4% incidence in the rhFSH group. With regard to another safety endpoint, no patients tested positive for adenosine deaminase (ADA) in the rhFSH-CTP group. The results demonstrated that the product had a comparable safety profile to pregnancy outcomes and newborn information in the control group, indicating its suitability for use.